(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this work, we introduce maximal sets and amicable sets in a paradistributive latticoid. We present a few number of examples and counter-examples for them, prove some algebraic properties on them. Also, we define center of a paradistributive latticoid and prove that it is equal to the intersection of all maximal sets. Finally, we obtain some necessary and sufficient conditions for a paradistributive latticoid to become relatively complemented.